2011
DOI: 10.1105/tpc.111.087395
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Cytokinin Mutants and Regulation of Cytokinin Metabolic Genes Reveals Important Regulatory Roles of Cytokinins in Drought, Salt and Abscisic Acid Responses, and Abscisic Acid Biosynthesis  

Abstract: Cytokinins (CKs) regulate plant growth and development via a complex network of CK signaling. Here, we perform functional analyses with CK-deficient plants to provide direct evidence that CKs negatively regulate salt and drought stress signaling. All CK-deficient plants with reduced levels of various CKs exhibited a strong stress-tolerant phenotype that was associated with increased cell membrane integrity and abscisic acid (ABA) hypersensitivity rather than stomatal density and ABA-mediated stomatal closure. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

29
560
2
5

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 660 publications
(596 citation statements)
references
References 65 publications
(111 reference statements)
29
560
2
5
Order By: Relevance
“…This viewpoint is supported by data indicating that abcg22 and abcg40 mutants are drought-sensitive as a result of higher transpirational water loss resulted from diminished stomatal closure compared with WT plants (25,26). Additionally, recent studies reported that the constitutive overexpression of CKX genes, namely CKX1, CKX2, CKX3, and CKX4, resulted in higher ABA sensitivity, enhanced ABA response and improved drought and salt tolerance in transgenic Arabidopsis and tobacco plants (17,18). The transcriptome analysis conducted in the present study revealed that, among seven Arabidopsis CKX genes, four (CKX1, CKX2, CKX3, and CKX5) were down-regulated in the max2 mutant with and/or without being subjected to dehydration (Dataset S7).…”
Section: Discussionsupporting
confidence: 65%
See 4 more Smart Citations
“…This viewpoint is supported by data indicating that abcg22 and abcg40 mutants are drought-sensitive as a result of higher transpirational water loss resulted from diminished stomatal closure compared with WT plants (25,26). Additionally, recent studies reported that the constitutive overexpression of CKX genes, namely CKX1, CKX2, CKX3, and CKX4, resulted in higher ABA sensitivity, enhanced ABA response and improved drought and salt tolerance in transgenic Arabidopsis and tobacco plants (17,18). The transcriptome analysis conducted in the present study revealed that, among seven Arabidopsis CKX genes, four (CKX1, CKX2, CKX3, and CKX5) were down-regulated in the max2 mutant with and/or without being subjected to dehydration (Dataset S7).…”
Section: Discussionsupporting
confidence: 65%
“…Whereas ABA and SL promote the senescence of leaves, CK delays leaf senescence (30,31). On the other hand, ABA (32) and SL (the present study) act as positive regulators of stomatal closure and thus stress response, whereas CK acts as a negative regulator of the same process (18,33). Importantly, results of the present study demonstrate the potential for the use of genetic engineering to improve the stress tolerance of crop plants by manipulating SL biosynthesis and/or SL signaling as suggested by the enhanced drought tolerance exhibited by WT plants sprayed with SL (Fig.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations